Fitting in and getting fit: a post-structuralist analysis of athletes' experiences of less disciplinary coaching practices. Issue 3 (2nd September 2021) - Konoval, Timothy; Denison, Jim; Mills, Joseph
ABSTRACT: Over the last two decades a number of coaching researchers have used post-structuralism to show how strict training protocols can limit athletes' performances and development. To counter problematic effects from highly disciplinary practices, Denison and colleagues have called for coach developers to assist coaches to implement less disciplinary coaching practices. Although the head coach is central in this work, understanding how athletes experience less disciplinary coaching practices is critical. Towards this end, we interviewed 14 university endurance runners after the first author worked collaboratively with their head coach to help him learn how to develop and implement a number of practices that were less informed by discipline's techniques and instruments. Despite making these changes, our findings revealed that the ongoing presence of a range of normalising and objectifying processes tied to dominant understandings of effective coaching and athlete development continued to exert their influence on the athletes. In this respect, designing and implementing less disciplinary coaching practices was not enough to challenge the long-standing legacy of discipline within endurance running. This led us to conclude that undoing the effects of discipline requires a much more concerted pedagogical effort from coaches, and as such, greater support and collaboration from coach developers.